Community Effects on Elderly Health: Evidence from CHARLS National Baseline - James P. Smith; Meng Tian; Yaohui Zhao (Institute for the Study of Labor (IZA), 2013)
There is increasing interest in neighborhood or area effects on health and individual development. China, due to its vast regional variations in health infrastructure and geography and relative immobility of older residents, provides a rare opportunity to study such effects. Utilizing China Health and Retirement Longitudinal Study (CHARLS) baseline survey 2011-2012 which covered over 17,000 individuals in 450 randomly selected communities/villages, this paper addresses two questions: whether community/village characteristics matter for individual health and SES (Socio-Economic Status), and why they matter. Our statistical results indicate that community/village characteristics have strong associations with individual health and SES.
Keywords: I10; I14; 330; China; neighborhood effects; health